2005
DOI: 10.1074/jbc.m502956200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Intracellular Ca2+ Levels in Nonsteroidal Anti-inflammatory Drug-induced Apoptosis

Abstract: We recently reported that nonsteroidal anti-inflammatory drug (NSAID)-induced gastric lesions involve NSAID-induced apoptosis of gastric mucosal cells, which in turn involves the endoplasmic reticulum stress response, in particular the up-regulation of CCAAT/enhancer-binding protein homologous transcription factor (CHOP). In this study, we have examined the molecular mechanism governing this NSAID-induced apoptosis in primary cultures of gastric mucosal cells. Various NSAIDs showed membrane permeabilization ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 54 publications
6
96
0
Order By: Relevance
“…BAPTA-AM also inhibited the GRP78 upregulation caused by nimesulide or diclofenac but not by indomethacin. We recently showed that all of NSAIDs tested (including nimesulide and diclofenac) increased the intracellular Ca 2 þ level (Tomisato et al, 2004a;Tanaka et al, 2005). Since indomethacin absorbed fluo-3 fluorescence (530 nm), we could not measure the intracellular Ca 2 þ level in the presence of indomethacin by the assay system using fluo-3 (Tanaka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…BAPTA-AM also inhibited the GRP78 upregulation caused by nimesulide or diclofenac but not by indomethacin. We recently showed that all of NSAIDs tested (including nimesulide and diclofenac) increased the intracellular Ca 2 þ level (Tomisato et al, 2004a;Tanaka et al, 2005). Since indomethacin absorbed fluo-3 fluorescence (530 nm), we could not measure the intracellular Ca 2 þ level in the presence of indomethacin by the assay system using fluo-3 (Tanaka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mizushima et al clearly showed that the primary targets of NSAIDs in the induction of necrosis and apoptosis are the cytoplasmic membranes. 33,35) In addition, Kato et al reported that excessive NO production via iNOS is related to an increased ulcerogenic response to NSAIDs including loxoprofen and indomethacin. 11,40) We show that the expression of iNOS mRNA and NO production in the gastric mucosa of normal and AA rats are increased by the administration of loxoprofen, and that these increases are significantly higher than those that occur in normal rats administered loxoprofen.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] However, it has been reported that NSAIDs induce necrosis and apoptosis in cultured gastric mucosal cells and in the gastric mucosa in a manner independent of COX inhibition, [33][34][35][36][37] and that the total inhibition of PG production in the stomach causes very little gastric damage in rats. 38) Therefore it is now believed that the inhibition of COX by NSAIDs is not the sole explanation for the gastrointestinal side effects of NSAIDs, 39) and it is assumed that other mechanisms in addition to PG deficiency are involved in the gastric ulcerogenicity of NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism whereby some NSAIDs are able to induce ER stress and apoptosis in gastric mucosal cells could be an increase in intracellular calcium levels secondary to membrane permeabilization (Tanaka et al. 2005). …”
Section: Introductionmentioning
confidence: 99%